Chronic Viral Hepatitis Diagnosis and Therapeutics - Shetty, Kirti; Wu, George Y.; SpringerLink (Online service) (Totowa, NJ : Humana Press, 2010)
Chronic viral hepatitis affect hundreds of millions of people worldwide, and each year millions more people become infected. In Chronic Viral Hepatitis, Second Edition, a panel of distinguished clinicians and clinical investigators build upon the first edition by comprehensively reviewing all the relevant new information regarding resistance, side effects, and therapies for chronic viral hepatitis. The text covers recent advances in the understanding of pathogenesis of viral hepatitis while discussing promising agents in development for its treatment. The authors devote special attention to reactivation of hepatitis B with chemotherapy and immunosuppression, herbal and non-traditional therapies, chronic viral hepatitis in the pediatric population, and immunology and immunotherapy of HCV and provide relative costs for all diagnostic and therapeutic options. Authoritative and up-to-date, Chronic Viral Hepatitis, Second Edition offers today's gastroenterologists, internists, hepatologists, and infectious disease specialists a practical guide to the recognition, diagnosis and treatment of chronic viral hepatitis from a multidisciplinary approach.
Molecular Virology of Hepatitis B and C: Clinical Implications -- Epidemiology, Risk Factors, and Natural History of Chronic Hepatitis C -- Current and Future Therapy of Chronic Hepatitis C -- Hepatitis C in Special Populations -- Extrahepatic Manifestations of Chronic Hepatitis C Infection -- Anti-HCV Agents in Development -- Epidemiology, Screening, and Natural History of Chronic Hepatitis B Infection -- Current Treatment of Chronic Hepatitis B -- Management of Patients Co-Infected with Chronic Hepatitis B (CHB) and the Human Immunodeficiency Virus (HIV) -- Management of Antiviral Resistance in Chronic Hepatitis B -- Herbal and Non-Traditional Therapies for Viral Hepatitis -- Hepatitis B Reactivation in the Setting of Chemotherapy and Immunosuppression -- Support of Patients During Antiviral Therapy for Hepatitis B and C -- Viral Hepatitis, A Through E, In Pregnancy -- Chronic Viral Hepatitis and Liver Transplantation -- Treatment of Viral Hepatitis in Children - 2008 -- Viral Hepatitis and Hepatocellular Carcinoma -- Hepatitis B Vaccines -- T-Cell-Mediated Immunity and Immunotherapy of Chronic Hepatitis C.
Keywords: Medicine; Gastroenterology; Medicine & Public Health; Gastroenterology